GAMBARAN HISTOPATOLOGIS DARI BIOPSI KULIT MULTIPEL LESI KULIT BERBEDA PADA PASIEN KUSTA TIPE BORDERLINE TUBERCULOID - Sutisna, Frizam Dwindamuldan; Gunawan, Hendra (Media Dermato-Venereologica Indonesiana, 2024)
The histopathological examination helps in prompt diagnosis and type of disease in some cases of leprosy. Determination of the biopsy site on the skin lesion is important. We report a case of borderline tuberculoid (BT) leprosy in a 54-year-old female who complained of numb red patches on the right forearm. From physical examination, three confluent hypoesthetic round shapes and annular erythematous macules, accompanied with one satellite lesion on the right forearm were found. The bacteriological examination revealed no acid-fast bacteria. Multiple skin biopsies were performed on round, annular, and satellite lesions. Histopathological features of the round erythematous macule demonstrated atrophic epidermis, lymphocyte infiltration, with epithelioid granulomas in the dermis, which supported BT leprosy. Histopathological features of the annular and satellite lesions showed lymphocyte infiltration in the dermis, perivascular, around the eccrine glands, and hair follicles, which corresponded to indeterminate leprosy. In leprosy, the concordance between histopathological and clinical features shows varying results. Multiple skin biopsies should be performed for multiple different skin lesions. The diagnosis of BT leprosy was established in this case after a clinicopathological correlation was done. In a leprosy patient, multiple skin biopsies obtained from different skin lesions could reveal a varied histopathological picture. Therefore, clinical and pathological correlation is needed in order to establish the diagnosis.